Rekonstruksi Pembelajaran Fisika Menggunakan Pendekatan Konstruktivisme Sebagai Implementasi Revolusi Sains Thomas Kuhn - Fuadi, Muhammad Ashar; Shaunata, Via Amalia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Thomas Samuel Kuhn is a physicist as well as a philosopher who contributed a lot of his thoughts in the development of science. His biggest contribution to the development of science is the Scientific Revolution, which is the drastic change that has taken place in the development of science. This research focuses on teaching physics, especially in the constructivism approach. The Constructivism approach itself is one type of approach that is able to ignite the critical spirit of students. The purpose of this research is to build students' critical thinking in Physics Learning using the Constructivism Approach as a form of implementation of the Science Revolution that has been proclaimed by Thomas Kuhn. The method or approach used in this research is a qualitative approach, which is an approach oriented to the theoretical values of an event. While the nature of this research is descriptive-analytic, which is a method used to provide an accurate picture of something that is happening in society. The results of this study indicate that in learning Physics, students are able to think critically by using the Constructivism Approach. The critical spirit of students can be seen by the activeness of students in discussions.